Analysis Of The Determinants Of Financial Distress In Technology Sector Companies On The Indonesia Stock Exchange For The 2019-2022 Period - Aini, Fuji Asih; Ari Andika; Didik Gunawan; Willy Cahyadi (SEAN Institute, 2024)
Companies in the technology sector tend to experience fluctuations in their financial performance. This research aims to determine the effect of liquidity, leverage and profitability on the occurrence of financial distress in technology sector companies from 2019 to 2022. This research uses quantitative research methodology and uses purposive sampling in taking samples. The testing methodology used is panel data regression, using a dataset consisting of 64 data points and carried out through the use of the E-Views 10 program. Research findings show that variables such as liquidity, leverage, and profitability do not have any influence on the likelihood of a financial disaster. There are other influencing factors such as government policies during the Covid 19 pandemic in the form of WFH and the macroeconomic situation such as interest rate hikes.